Parent-infant interaction. - Symposium on the Parent-Infant Relationship, London, Eng.; Ciba Foundation (Amsterdam ; New York : Elsevier : Excerpta Medica, 1975)
Proceedings of the symposium on The Parent-Infant Relationship held at the Ciba Foundation, London, 5th-7th Nov. 1974.
Proceedings of the symposium held at the Ciba Foundation, London, 5th-7th Nov. 1974.
Includes bibliographies and indexes.
Keywords: Infant psychology -- Congresses; Parent and infant -- Congresses; Infant, Newborn; Mother-Child Relations